2021
DOI: 10.18794/aams/142128
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar pulsed radiofrequency neuromodulation of median nerve for treatment of carpal tunnel syndrome – a preliminary study

Abstract: WstępWyniki chirurgicznego odbarczenia nerwu pośrodkowego u części chorych z zespołem cieśni nadgarstka są niezadowalające. Celem pracy jest ocena wczesnych wyników leczenia zespołu cieśni nadgarstka (<i>carpal tunnel syndrome</i> – CTS) za pomocą bipolarnej neuromodulacji nerwu pośrodkowego (<i>median nerve</i> – MN) z użyciem prądu o częstotliwości radiowej w trybie pulsacyjnym (<i>pulsed radiofrequency</i> – PRF).Materiał i metodyLeczeniu poddano 15 dorosłych pacjentów z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In total, 12 studies were further excluded as they had not yet been completed (n = 2), performed the wrong intervention (n = 2), had the wrong study design (n = 5), included the wrong patient population (n = 3), leaving a final number of eight studies for inclusion (Figure 1). Of the final included studies, one was a case report, 6 three studies were retrospective in nature, 1,7,8 and four were prospective [9][10][11][12] (with three being randomized trials [9][10][11] ). Six of the eight studies were available in full-text, 1,6,8,[10][11][12] whereas two were available in abstract-only form from the same conference.…”
Section: R E Su Lt Smentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 12 studies were further excluded as they had not yet been completed (n = 2), performed the wrong intervention (n = 2), had the wrong study design (n = 5), included the wrong patient population (n = 3), leaving a final number of eight studies for inclusion (Figure 1). Of the final included studies, one was a case report, 6 three studies were retrospective in nature, 1,7,8 and four were prospective [9][10][11][12] (with three being randomized trials [9][10][11] ). Six of the eight studies were available in full-text, 1,6,8,[10][11][12] whereas two were available in abstract-only form from the same conference.…”
Section: R E Su Lt Smentioning
confidence: 99%
“…Of the final included studies, one was a case report, 6 three studies were retrospective in nature, 1,7,8 and four were prospective [9][10][11][12] (with three being randomized trials [9][10][11] ). Six of the eight studies were available in full-text, 1,6,8,[10][11][12] whereas two were available in abstract-only form from the same conference. 7,9 From a search of the reference sections of included studies, we found no additional studies that satisfied the inclusion criteria for this review.…”
Section: R E Su Lt Smentioning
confidence: 99%
See 3 more Smart Citations